ADE and hyperinflammation in SARS-CoV2 infection- Comparison with dengue hemorrhagic fever and feline infectious peritonitis (2020)
The COVID-19 pandemic has rapidly spread around the world with significant morbidity and mortality in a subset of patients including the elderly. The poorer outcomes are associated with ‘cytokine storm-like’ immune responses, otherwise referred to as ‘hyperinflammation’. While most of the infected individuals show minimal or no symptoms and recover spontaneously, a small proportion of the patients exhibit severe symptoms characterized by extreme dyspnea and low oxygen tissue levels, with extensive damage to the lungs referred to as acute respiratory distress symptom (ARDS). The consensus is that the hyperinflammatory response of the host is akin to the cytokine storm observed during sepsis and is the major cause of death. Uncertainties remain on the factors that lead to hyperinflammatory response in some but not all individuals. Hyperinflammation is a common feature in different viral infections such as dengue where existing low-titer antibodies to the virus enhances the infection in immune cells through a process called antibody-dependent enhancement or ADE. ADE has been reported following vaccination or secondary infections with other corona, Ebola and dengue virus. Detailed analysis has shown that antibodies to any viral epitope can induce ADE when present in suboptimal titers or is of low affinity. In this review we will discuss ADE in the context of dengue and coronavirus infections including Covid-19.